Discursividades da/sobre a ditadura militar em uma hemeroteca digital - Lampoglia, Francis (2012)
This work aims to study the discourse functioning of the brazilian military dictatorship in the headlines and the Última Hora's journal reports, using the french discourse analysis theory, specially inscribed around Michel Pêcheux and the studies of Mikhail Bakhtin. The way the subject is positioned in relation to the military dictatorship and how this positioning is reflected in the digital newspaper libraries that stores the papers constitutes the problem of this study , which has as its theoretical pillars of the sociohistorical conditions of production of meanings and discoursive memory underlying all sayings. Therefore, this work will analyze the corpus of headlines and reports from the collection of digitized periodic Última Hora from 1964 to 1969, copies of which are available on the website of the Public Archives of the State of Sao Paulo. To make a counterpoint, also have added to the corpus of newspaper headlines and reports Folha de S. Paulo (1965), Jornal do Brasil (1964), and O Estado de S. Paulo (1973 to 1974), available in their electronic holdings. Analysing the selected clippings, we can assume how memory and archive discoursive, which are inserted in a certain socio-historical context, inscribes itself in this discoursivity and influences the production of meaning. Note that these movements of meanings in clippings includes a way to think about how language is constantly struck by history, how the senses migrate according to the position the subject occupies as the circulation of words in the headlines and reports newspapers dialogues with the senses in the different socio-historical contexts